Using ultrasound to teach living anatomy to non-medical graduate students. - Bullen, Theresa R.; Brown, Kirsten; Ogle, Kathleen; Liu, Yiju Teresa; Jurjus, Rosalyn A. (Surgical & Radiologic Anatomy, 2020)
Purpose: Ultrasound technology is used to supplement gross anatomy instruction in many medical sciences programs. However, this technology is not common practice for anatomy instruction in nonmedical graduate-level courses. Ultrasound sessions provide a clear view of local anatomy and could help graduate students transfer anatomical content from a didactic context onto a living, moving body. This approach to instruction complements the rapidly evolving technological advances in science education and may assist with spatial understanding, knowledge retention, and student engagement. The main objective of this article was to describe the methods used to incorporate ultrasound sessions into a graduate level gross anatomy course. Methods: The goal of the curricula was to use ultrasound technology to create a supplemental hands-on and engaging method of learning anatomy that would appeal to graduate students and possibly reinforce content. Graduate students participated in three interactive, 2-h-long ultrasound sessions that corresponded to their gross anatomy lecture material. Results: Questionnaire results showed that students overwhelmingly believed that the ultrasound sessions were beneficial and that ultrasound technology should be used for anatomical instruction in graduate programs. While students found the sessions to be helpful, they sought more and longer sessions with smaller group sizes. Conclusion: Overall, this article describes the methods used to incorporate multimodal learning into a graduate level anatomy course and found that students supported the methods as a potentially effective and engaging way to supplement traditional gross anatomy lectures and practical laboratory sessions.